NEED ANALYSIS OF INDONESIAN TEACHING MATERIALS AT ISLAMIC RELIGIOUS UNIVERSITIES - Firman Firman (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The instructional materials have a significant impact on the learning process. This study aimed to determine the demand for Indonesian language teaching materials in Indonesian Islamic religious colleges. This study was conducted at the Palopo State Islamic Institute with the participation of 2018 madrasah ibtidaiyah teacher education program students who had attended Indonesian language lectures the previous semester. This study included 84 students and six instructors of the Indonesian language. This survey-based study employs a qualitative descriptive design. In the form of questionnaires, observations, and interview guidelines, data collection instruments. The data were analyzed qualitatively and descriptively. According to a study, students and professors require textbooks incorporating Islamic perspectives. Therefore, the curriculum includes Islamic history texts, lectures or sermons, Quranic and Hadith verse quotations and translations, articles, and Islamic literary works. These findings can be considered when developing Indonesian language instructional materials for IAIN Palopo and other Indonesian Islamic religious universities.